Um homem em toda a verdade da natureza: linguagem e escrita de si em Jean-Jacques Rousseau - Lucas Mello Carvalho Ribeiro (2011)
The present dissertation aims to demonstrate that the writing which sustains J.-J. Rousseaus autobiographical project, especially that of the Confessions, is conceived so as to bypass the problems, diagnosed by the philosopher (in different texts prior to the confessional undertaking), concerning language and its use by the corrupted man. In order to accomplish this purpose, we will try, firstly, to delimitate why and in what degree language imposes itself as a problem to Rousseau. This will lead us to reconstruct the meanders of its genesis and posterior degradation. That being done, there will remain the task of clarifying the nature of the Rousseaunian self-writing, unraveling the (philosophical) motives that engender it, as well as the conceptual landmarks that ground it. Through this entire démarche, some main topics will be contemplated, such as: (i) the bond that ties together, in Rousseau, language and society; (ii) the relations between language and passions; (iii) the statute of gesture, speech and writing throughout Rousseaus work.